Acutely damaged axons are remyelinated in multiple sclerosis and experimental models of demyelination. Issue 8 (31st May 2017) - Schultz, Verena; van der Meer, Franziska; Wrzos, Claudia; Scheidt, Uta; Bahn, Erik; Stadelmann, Christine; Brück, Wolfgang; Junker, Andreas
Abstract: Remyelination is in the center of new therapies for the treatment of multiple sclerosis to resolve and improve disease symptoms and protect axons from further damage. Although remyelination is considered beneficial in the long term, it is not known, whether this is also the case early in lesion formation. Additionally, the precise timing of acute axonal damage and remyelination has not been assessed so far. To shed light onto the interrelation between axons and the myelin sheath during de‐ and remyelination, we employed cuprizone‐ and focal lysolecithin‐induced demyelination and performed time course experiments assessing the evolution of early and late stage remyelination and axonal damage. We observed damaged axons with signs of remyelination after cuprizone diet cessation and lysolecithin injection. Similar observations were made in early multiple sclerosis lesions. To assess the correlation of remyelination and axonal damage in multiple sclerosis lesions, we took advantage of a cohort of patients with early and late stage remyelinated lesions and assessed the number of APP‐ and SMI32‐ positive damaged axons and the density of SMI31‐positive and silver impregnated preserved axons. Early de‐ and remyelinating lesions did not differ with respect to axonal density and axonal damage, but we observed a lower axonal density in late stage demyelinated multiple sclerosis lesions than in remyelinated multiple sclerosis lesions. Our findings suggest that remyelination may not only be protective over a long period of time, but may play an important role in the immediate axonal recuperation after a demyelinating insult. Main Points: In multiple sclerosis lesions (MS) and distinct experimental models of de‐ and remyelination, we observed efficient remyelination of damaged axons, suggesting axon protection by remyelination both in early and late stage lesions.